Perinatal outcome in normal pregnant women with incidental thrombocytopenia at delivery - Ying-Hsuan Lin; Liang-Ming Lo; Ching-Chang Hsieh; Tsung-Hung Chiu; T'sang-T'ang Hsieh; Tai-Ho Hung (Elsevier, 2013)
Objective: To investigate the perinatal outcomes of women who suffered from thrombocytopenia at delivery but did not have other diseases during pregnancy. Materials and Methods: We considered all singleton deliveries after 24 weeks of gestation at Chang Gung Memorial Hospital, Taipei, Taiwan between 2001 and 2010. Women were excluded from this study if they suffered from any of the following conditions: chronic hypertension, hepatitis, acute fatty liver, liver cirrhosis, nephropathy, overt diabetes mellitus, connective tissue disease, systemic lupus erythematosus, or immune thrombocytopenia. Pregnancies complicated by gestational hypertension, preeclampsia, or fetal anomalies during gestation were also excluded. A total of 18,384 deliveries were included for analysis. Women were divided into three groups according to platelet count at admission. Results: A total of 787 pregnancies (4.3%) were complicated by thrombocytopenia. Thrombocytopenic women had a significantly higher rate of cesarean delivery compared to women who did not have this condition. No other differences were observed among these three groups regarding the rates of adverse pregnancy outcomes. Conclusions: The results indicate that women who suffered from incidental thrombocytopenia at delivery but did not have other diseases during pregnancy were not at increased risk for adverse pregnancy outcomes.